Urinary stone composition analysis and clinical characterization of 1520 patients in central China - Daling Zhang (Nature Portfolio, 2021)
Abstract A total of 1520 patients with urinary stones from central China were collected and analysed by Fourier transform infrared spectroscopy between October 1, 2016 and December 31, 2019. For all patients, age, sex, comorbidities, stone location, laboratory examination and geographic region were collected. The most common stone component was calcium oxalate (77.5%), followed by calcium phosphate (8.7%), infection stone (7.6%), uric acid (UA) stone (5.3%)and cystine (0.9%). The males had more calcium oxalate stones (p < 0.001), while infection stone and cystine stones occurred more frequently in females (p < 0.001). The prevalence peak occurred at 41–60 years in both men and women. UA stones occurred frequently in patients with lower urinary pH (p < 0.001), while neutral urine or alkaline urine (p < 0.001) and urinary infection (p < 0.001) were more likely to be associated with infection stone stones. Patients with high levels of serum creatinine were more likely to develop UA stones (p < 0.001). The proportion of UA stones in diabetics was higher (p < 0.001), and the incidence of hypertension was higher in patients with UA stones (p < 0.001). Compared to the other types, more calcium oxalate stones were detected in the kidneys and ureters (p < 0.001), whereas struvite stones were more frequently observed in the lower urinary tract (p = 0.001). There was no significant difference in stone composition across the Qinling-Huaihe line in central China except UA stones, which were more frequently observed in patients south of the line (p < 0.001).